PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DALAM PENGGUNAAN JASA EXPEDISI J&T CARGO CABANG SUKODONO DI SIDOARJO - Fauziyah, Nur Lailik; Mulyati, Awin (Research Journal of Social Science and Economics, 2025)
This research was conducted at J&T Cargo Sukodono Branch in Sidoarjo. The Service Quality variable does not have a significant effect on Consumer Satisfaction. This is evident from the results of the t count on the Service Quality variable (X2) which is smaller than the t table with Consumer Satisfaction at J&T Cargo Sukodono Branch, Sidoarjo City. The price variable has a significant effect on consumer satisfaction. This is evident from the results of the t-count value that is greater than t-table. There is a positive and significant effect between price on consumer satisfaction at J&T Cargo Sukodono Branch, Sidoarjo City. Because at the J&T Cargo Expedition, the Sukodono Branch also adjusts the needs for shipping goods between outside the city at affordable prices. This study aims to analyze the effect of price and service quality on consumer satisfaction, J&T Cargo delivery services, Sukodono Branch, Sidoarjo City. The type of research used in research is Quantitative. The population in this study were consumers of J&T Cargo delivery services, Sukodono Branch, Sidoarjo City, with a sample of 100 respondents. The results of this study indicate that the price variable has an influence on consumer satisfaction while the service quality variable has no influence on consumer satisfaction. Keywords : Price, Service Quality, Consumer Satisfaction